Chapter 8 Karl Marx and the Heroic Revolution - Farrell, John (Taylor & Francis, 2023)
Marx was a bitter opponent of feudal-aristocratic distinction and his vision of communism as the end-state of history is classically utopian, but he views the current world as a field in which progressive forces can advance only by class conflict. Thus Marx crystallizes the new, post-French Revolution phase in which utopian thinkers seek to transcend the utopian dilemma as a philosophical stance in order to regain practical access to heroic resources, including violence.